Congenital afibrinogenemia: from etiopathogenesis to challenging clinical management. Issue 7 (2nd July 2016) - Stanciakova, Lucia; Kubisz, Peter; Dobrotova, Miroslava; Stasko, Jan
ABSTRACT: Introduction : Congenital afibrinogenemia belongs to the group of autosomal recessive bleeding disorders and represents the absolute deficiency of fibrinogen detected by an antigenic test. This can lead to severe clinical manifestations of the disorder. Therefore, it is very important to take afibrinogenemia into account in the process of the differential diagnostics of the patients. Areas covered : The authors provide a summary of currently available literature about afibrinogenemia. They collected the information from the scientific journals dedicated to thrombosis and hemostasis and searched world-wide databases. Expert commentary : The most frequent clinical manifestation of this disorder is mucosal bleeding, but musculoskeletal bleeding pattern, gynecologic and obstetric issues, spontaneous bleeding, episodes provoked by minor injury or any other intervention, and even paradoxical thromboembolic events have been published. Afibrinogenemia is the consequence of mutations of the homozygous or compound heterozygous type in gene FGA, FGB or FGG encoding fibrinogen. Pregnant women with a family history, or with a history of consanguinity ought to be properly counselled. However, primary prophylaxis of bleeding events is not suggested. The article deals with actual information about afibrinogenemia contributing to its early diagnosis and effective treatment, which in many cases requires multidisciplinary approach.